Anthropogenic disturbances consistently favor the high-yield strategists of soil bacterial community in the Eurasian steppe - Yi Fan (BMC, 2021)
Abstract Purpose Multiple anthropogenic disturbances, such as climate warming and nitrogen deposition are affecting terrestrial ecosystems. Different disturbances may have some consistent effects on the soil microbial community, which remains largely unexplored. Methods We mimicked 16 anthropogenic disturbances in a steppe ecosystem, and measured the absolute abundance and taxonomic composition of soil bacterial communities with qPCR and amplicon sequencing, respectively. Results We found that while the absolute abundance of each of the four dominant bacterial phyla did not show a consistent response to these disturbances, that of the five subdominant phyla showed a consistent increase. Meanwhile, these disturbances consistently stimulated the relative abundances of metabolic functions for high-growth-yield, including the transport/metabolism of amino acids and carbohydrates. Stochastic processes (e.g., random birth) played more critical roles in structuring the subdominant than dominant phyla, and the disturbances promoted the stochastic processes. Conclusions Overall, the high-yield traits and stochasticity of subdominant phyla led to their positive responses to disturbances. Furthermore, our findings indicate that the intensifying human activities are likely to cause a high-yield-strategies-toward shift in soil microbial composition in the Eurasian steppe ecosystem.